The effect of white noise on psychological stress while performing cognitive tasks and its correlation to performance - Fox, Dan; Karic, Berina; Ash, Alex; Dietz, Jason; Swiggum, Amanda (Journal of Advanced Student Sciences (JASS), 2015)
It is common for young adults to resort to illicit means, such as using non-prescription stimulants, to improve their performance in school. Our study investigated the effects that white noise masked over ambient noise during cognitive tasks had on stress, in addition to any correlation with performance, to determine if white noise is an effective study tool to improve performance and lower stress. We hypothesized stress would be lowest under white noise masked conditions, while test performance would be highest. Participants were assigned to one of three listening conditions: white noise, ambient (negative control), or music (positive control). Three physiological stress indicators (blood pressure, pulse, and electrodermal activity) were recorded during two separate tests on concentration and planning skills, as well as the score achieved on the two tests to measure performance. The p-values from the t-tests from the ambient and the white noise conditions inferred no significant correlations between any of the physiological measurements (p>0.05). This may mean listening to white noise does not lower stress, contrary to our hypothesis; but the convergence of all three conditions’ peak locations on density plots may mean all data recordings are invalid, possibly due to equipment error or a lack of predictive power of stress by the physiological responses. Additionally, the p-values from the t-tests from the ambient and the white noise conditions did not reveal any significant correlations between the scores on the planning or concentration tests (p>0.05). Thus, our data infers that listening to white noise does not correlate with performance in a mechanism not mediated by stress, yet further testing is needed to validate the physiological measurements obtained.
An article that appeared in JASS, issue 2015
Keywords: audio; blood pressure; cognitive function; cognitive processing; concentration; GSR; music; planning; pulse; stress; white noise